Assessing the Reliability of Causes of Death Reported by the Vital Registration System in Sri Lanka: Medical Records Review in Colombo. Issue 3 (October 2013) - Rampatige, Rasika; Gamage, Saman; Peiris, Sharika; Lopez, Alan D
Information on causes of death is critical for informed decision making in the health sector. This paper reports findings from a study that measured the accuracy of registered causes of death and quality of medical records for a sample of deaths occurring in hospitals in Colombo, Sri Lanka. Five physicians, trained in medical certification of cause of death, reconstructed death certificates for hospital deaths from medical records and assessed the quality of medical records for this purpose. The majority of medical records were found to be of average quality. Concordance between the underlying cause of death in the vital registration data and that from the 'gold standard' (medical records review) diagnosis was 41.4% ( n =249). The sensitivity of all leading causes of death and positive predictive value were below 67%. Major misclassification errors were found in identifying deaths due to vascular diseases and diabetes mellitus. Certified causes of death in Sri Lanka are frequently incorrect, thus limiting their value for health policy and for monitoring progress towards development goals. Sri Lanka, and other countries at a similar level of statistical development, should consider periodically conducting research to evaluate the quality of cause of death reporting at both local and national levels.